Toxic Relationships and Attachment Styles Among Young Adults: A Qualitative Research - Rahmadianti, Yundira Putri; Fajrinaldi (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
Toxic relationships, characterized by patterns of domination, manipulation, and recurrent conflict, can significantly damage individuals’ emotional well-being and shape unhealthy attachment styles. However, research gaps remain regarding how young adults who have experienced toxic romantic relationships reflect on their attachment patterns and how these patterns evolve in subsequent relationships. This research aims to explore the experiences of young adults who have survived toxic relationships and to understand how these experiences influenced their attachment styles and interpersonal communication patterns. Using a qualitative approach with Interpretative Phenomenological Analysis (IPA), data were collected through semi-structured interviews with three informants aged 24–32 years who had ended toxic relationships at least one year prior. The results reveal that all informants initially experienced positive communication and affection with their partners, but later faced controlling, aggressive, or manipulative behaviors that led to insecure attachment styles characterized by fear, dependence, and lack of autonomy. The research concludes that toxic relationships leave a strong impact on attachment styles and negatively affect the victims’ mental well-being. However, further analysis of interview data reveals that individuals can develop healthier patterns when they gain awareness and engage in more constructive communication in future relationships. These findings have both theoretical and practical implications to enrich understanding of Attachment Theory in the context of toxic romantic relationships among young adults and offer valuable insights for counselors, therapists, and educators to support survivors in rebuilding secure, healthy interpersonal relationships.